Prediction of relative density of carbonate soil by way of a dynamic cone penetration test. Issue 2 (21st May 2019) - Lin, L.; Li, S.; Liu, X. L.; Chen, W. W.
Abstract : Relative density is an important parameter in geotechnical engineering and the dynamic cone penetration test has been widely used for its assessment. The currently established relationships between the dynamic penetration index and relative density might not be suitable for carbonate sediments due to their unique engineering properties. Therefore, 18 dynamic cone penetration model tests were conducted for carbonate coarse-grained soils. Simultaneously, 18 other laboratory model tests for quartz soils with similar gradations were carried out for comparison. The test results indicate that under the same relative density, the dynamic penetration index of carbonate coarse-grained soils is lower than that of quartz soils. In addition, the particle size and gradation of soils exert a greater influence on the dynamic penetration index of carbonate coarse-grained soils. Based on the test results and considering the influence factors mentioned above, two relationships between the dynamic penetration index and relative density are presented for carbonate and quartz soils, and these relationships could be used to evaluate the properties of soil backfills and base materials.